Surface integrity and wear behavior of 300M steel subjected to ultrasonic surface rolling process - Dang, Jiaqiang; Zhang, Heng; An, Qinglong; Lian, Guohui; Li, Yugang; Wang, Haowei; Chen, Ming (Surface & coatings technology, 2021)
In this work, the influences of ultrasonic surface rolling process (USRP) on the surface integrity and wear resistance of 300M steel samples were comprehensively studied. The effects of processing pass on the surface integrity were analyzed in term of surface topography, surface roughness (Ra), superficial microstructure, microhardness, and residual stresses. The results indicated that 10-pass USRP treatment can generate a highly smooth surface with Ra ≈ 7 nm. Nanocrystalline and ultrafine crystalline structures were produced in the surface layer. Significant compressive residual stress with a maximum value of about −950 MPa and a depth of about 800 μm was introduced into the sample surface. The comprehensive effects of grain refinement, work hardening, and compressive residual stress improved the surface hardness by about 30.9%, which obviously enhanced the wear resistance of 300M steel. It is noteworthy that the improvements of surface integrity and wear resistance of 300M steel brought about by USRP tend to be saturated along with the increase of processing passes. •Excellent surface integrity and wear resistance of 300M steel were obtained by USRP.•USRP could generate a smooth surface with Ra of 7 nm under high processing passes.•Martensite phase transformation was observed on the surface layer with increasing processing passes.•Variation of surface integrity by USRP becomes saturated with increasing processing passes.